Nonlinear wave-particle interaction behaviors driven by energetic ions in the HL-2A Tokamak. (12th July 2018) - Hou, Y.M.; Chen, W.; Yu, Y.; Lesur, M.; Duan, X.R.; Xu, M.; Ye, M.Y.
Abstract: Frequency chirping properties of Alfvén modes driven by energetic ions in HL-2A have been analyzed with a method based on the so-called Berk–Breizman model, which predicts that the interaction between wave, energetic ions and collision effects may exhibit steady-state, periodic, chaotic and explosive regimes. Nonlinear wave-particle interaction behaviors with chirping structures observed in HL-2A belongs to the chaotic regime. Those four typical unstable regimes are reproduced by a simulation code with two collision models: pure diffusion and pure Krook operator. As known, frequency shifts nonlinearly, from the linear eigenfrequency, as phase space holes and clumps move upward and downward respectively from original resonance region. In this paper, typical unstable chirping events observed in HL-2A are presented, and bulk plasma parameters are provided for the identification of TAEs, RSAEs and BAEs. Alfvén instabilities including TAEs with up-down and main-downward hooked chirping, RSAEs with up-sweeping and down-sweeping chirping, BAEs with up-down and main-downward chirping in HL-2A are discussed in this work. Comparing up-down and main-downward chirping plasma parameters of TAEs and BAEs, we assume that lower density, higher electron temperature would mean higher beam beta, stronger drive, and stronger collision operators. Furthermore, two codes based on BB model, -COBBLES and BOT, are applied to up-down TAEs, and both Krook and Fokker–Plank collision models are considered. Comparing the amplitude of perturbations between experimental observation and calculation, the -COBBLES with Fokker–Plank collision model yields better qualitative and quantitative agreement. Though the spectrum obtained by BOT code does not show good agreements with lifetime and frequency, it shows a qualitative agreement. As for TAEs with main-downward frequency chirping, only BOT with Fokker–Plank model could show a qualitative agreement. Comparing the collision operators of up-down and main-downward chirping, main-downward chirping correlated with stronger collision operators.